COMPARACION CITOGENETICA DE DOS POBLACIONES DE THOMASOMYS LANIGER LANIGER (THOMAS 1895) RODENTIA CRICETIDAE, 115 EN LOS PARAMOS DE CRUZ VERDE Y EL VERJON (2013)
Cell cultures from bone marrow and peripheral blood obtained by cardiac puncture were used to describe the karyotype of the field m o use Tomasomys laniger laniger in two populations found in the areas of Cruz Verde andEl V erjon, Cundinamarca, (Col.). C-banding and Giemsa staining allowed us to ascertain its diploid number 2n=24 with nine pairs of metacentric, two submetacentric and one acrocentric chromosomes; the fundamental number (FN) was 46. The X chromosomes have a heterochromatic markerband in the q arm; pair 10 has conspicuous satcllites and the Y is a large and uni-que acrocentric chromosome equivalent to more than 5% of the total length of the genome. Polymorphism was observed in and between the two populations. Cytogenetic characteristics of Th. laniger lani-ger differ from other species of the genus, and show a great deal of similarities to o"ther cricetids such as Cricetulus griseus.